Evaluation of pseudoephedrine pharmacy sales before and after mandatory recording requirements in Western Australia: a case study - Hattingh, H. Laetitia; Varsani, J.; Kachouei, L.; Parsons, Richard (BioMed Central Ltd, 2016)
Background: A community pharmacy real-time electronic recording program, ProjectSTOP, enables Australian community pharmacists to verify pseudoephedrine requests. In Western Australia the program was available for voluntary use from April 2007 and became mandatory November 2010. This case study explores the effectiveness of the program by reviewing the total requests for pseudoephedrine products, and the proportion of requests which were classified as ‘denied sales’ before and after mandatory implementation. Seasonal and annual trends in these measures are also evaluated. Methods: ProjectSTOP data recordings for Western Australia pharmacies between 1 December 2007 and 28 February 2014 were analysed. Data included a de-identified pharmacy number and date of each pseudoephedrine product request. The total number of requests and sale classification (allowed, denied, safety, or not recorded) were calculated for each month/pharmacy. The potential influence of mandatory reporting using ProjectSTOP was investigated using a Regression Discontinuity Design. Correlations between sales from the same pharmacy were taken into account by classifying the pharmacy number as a random effect. The main effects of year (continuous variable), and season (categorical variable) were also included in the model. Results: There was a small but steady decline in the total requests for pseudoephedrine per month per 100,000 population (per pharmacy) from the time of mandatory reporting. The number of denied sales showed a steady increase up until mandatory reporting, after which it showed a significant decline over time. Total sales were heavily influenced by season, as expected (highest in winter, least in summer). The seasonal pattern was less pronounced for denied sales, which were highest in winter and similar across other seasons. The pattern over time for safety sales was similar to that for denied sales, with a clear change occurring around the time of mandatory reporting. Conclusion: Results indicate a decrease in pseudoephedrine product requests in Western Australia community pharmacies. Findings suggest ProjectSTOP has been successful in addressing suspicious sales and potential diversion however ongoing data review is recommended.